Síntese, caracterização e avaliação do potencial antioxidante de compostos de L-triptofano com Mn (II), Ni (II), Cu (II) E Zn (II) - Mello, Genilza da Silva (2014)
L-Tryptophan (Trp) is classified as an essential amino acid with an indolic side chain. It can be found mainly in milk and dairy products, egg, salmon, potato and tomato. Trp is important to biological systems. It is used in the synthesis of serotonin, melatonin, niacin and kynurenine. Trp is an interesting ligand for the coordination chemistry due to different binding sites presented by the biomolecule and also for showing low toxicity and high purity (above 99% w/w), therefore, it can be used as ligand in metal complexes.Compounds with Trp were synthesized in the solid state with metals Mn2+, Ni2+, e Cu2+ e Zn2to evaluate some potential uses in others activities. The compounds were synthesized in the solid state by stoichiometric addition inaqueous solution containing M:Trp (1:2) . The characterization was evaluated by TG- DSC, XRD and FTIR. The DPPH’s reduction method was used to evaluate the antioxidant potential of the synthesized compounds. The thermoanalytical techniques couldsuggest the formation of compounds Mn(Trp)2·1,5H2O, Ni(Trp)2·3,5H2O, Cu(Trp)2 and Zn(Trp)2. The Mn(Trp)2·1,5H2O compound showed better antioxidant activity with the DPPH (24.59% ± 0.26) at the concentration of 250μM. The analysis of antioxidant activity has been used in research centers as the initial parameter for future applications in the pharmaceutical and food industry. From these results it can be suggested the use of new materials for other investigations, such as toxicity, clinical tests, pharmacokinetics and pharmacodynamics.